Development of Learning Tools to Improve Students Self-Efficacy - Muhammad Hidayat; Suvriadi Panggabean (JMEA : Journal of Mathematics Education and Application, 2022)
This research is included into development research type. This research uses a 4-D model (define, design, develop, and disseminate) Thiagarajan (1974). This research is organized by learning media and instruments, namely: the students handbook, the teachers handbook, lesson plan, the students exercise sheet, the students mathematical problem-solving ability test and self-efficacy questionnaires. Tests conducted on grade X as many as 26 people in Madrasah Aliyah Muhammadiyah (MAM) 1 Medan. The results of this research indicate that: Improvement of students' self efficacy after learning produces an average value of 84.5.